Quantitative Approaches to Fiscal Sustainability Analysis : A New World Bank Tool Applied to Turkey - van Wijnbergen, Sweder; Budina, Nina (World Bank, Washington, DC, 2012)
Fiscal sustainability analysis (FSA) is an important component of macroeconomic analysis. The authors review various quantitative approaches to FSA with a major objective to bring these approaches together and to present a user-friendly tool for FSA that reflects modern developments. They combine a dynamic simulations approach with a simplified version of the steady-state consistency approach. They also incorporate two different methods to deal with uncertainty: user-defined stress tests and stochastic simulations. The tool goes further by evaluating the required fiscal adjustment as a consequence of the stochastic realizations of the exogenous variables. Furthermore, the fiscal sustainability tool incorporates an endogenous debt feedback rule for the primary surplus, a fiscal policy reaction function. Besides outlining the theoretical framework, the authors also present a case study for Turkey.